Permafrost distribution map of San Juan Dry Andes (Argentina) based on rock glacier sites - Esper Angillieri, María Yanina (Journal of South American Earth Sciences)
Rock glaciers are frozen water reservoirs in mountainous areas. Water resources are important for the local populations and economies. The presence of rock glaciers is commonly used as a direct indicator of mountain permafrost conditions. Over 500 active rock glaciers have been identified, showing that elevations between 3500 and 4500 m asl., a south-facing or east-facing aspect, areas with relatively low solar radiation and low mean annual air temperature (−4 to 0 °C) favour the existence of rock glaciers in this region. The permafrost probability model, for Dry Andes of San Juan Province between latitudes 28º30′S and 32°30′S, have been analyzed by logistic regression models based on the active rock glaciers occurrence in relation to some topoclimatic variables such as altitude, aspect, mean annual temperature, mean annual precipitation and solar radiation, using optical remote sensing techniques in a GIS environment. The predictive performances of the model have been estimated by known rock glaciers locations and by the area under the receiver operating characteristic curve (AUROC). This regional permafrost map can be applied by the Argentinean Government for their recent initiatives which include creating inventories, monitoring and studying ice masses along the Argentinean Andes. Further, this generated map provides valuable input data for permafrost scenarios and contributes to a better understanding of our geosystem. Fil: Esper Angillieri, María Yanina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Juan. Centro de Investigaciones de la Geosfera y Biosfera. Universidad Nacional de San Juan. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones de la Geosfera y Biosfera; Argentina